Regulation of Lipolysis and Adipose Tissue Signaling during Acute Endotoxin-Induced Inflammation: A Human Randomized Crossover Trial - Rittig, Nikolaj (PLoS One, 2016)
BACKGROUND: Lipolysis is accelerated during the acute phase of inflammation, a process being regulated by pro-inflammatory cytokines (e.g. TNF-α), stress-hormones, and insulin. The intracellular mechanisms remain elusive and we therefore measured pro- and anti-lipolytic signaling pathways in adipocytes after in vivo endotoxin exposure. METHODS: Eight healthy, lean, male subjects were investigated using a randomized cross over trial with two interventions: i) bolus injection of saline (Placebo) and ii) bolus injection of lipopolysaccharide endotoxin (LPS). A (3)H-palmitate tracer was used to measure palmitate rate of appearance (Ra(palmitate)) and indirect calorimetry was performed to measure energy expenditures and lipid oxidation rates. A subcutaneous abdominal fat biopsy was obtained during both interventions and subjected to western blotting and qPCR quantifications. RESULTS: LPS caused a mean increase in serum free fatty acids (FFA) concentrations of 90% (CI-95%: 37–142, p = 0.005), a median increase in Ra(palmitate) of 117% (CI-95%: 77–166, p<0.001), a mean increase in lipid oxidation of 49% (CI-95%: 1–96, p = 0.047), and a median increase in energy expenditure of 28% (CI-95%: 16–42, p = 0.001) compared with Placebo. These effects were associated with increased phosphorylation of hormone sensitive lipase (pHSL) at ser(650) in adipose tissue (p = 0.03), a trend towards elevated pHSL at ser(552) (p = 0.09) and cAMP-dependent protein kinase A (PKA) phosphorylation of perilipin 1 (PLIN1) (p = 0.09). Phosphatase and tensin homolog (PTEN) also tended to increase (p = 0.08) while phosphorylation of Akt at Thr(308) tended to decrease (p = 0.09) during LPS compared with Placebo. There was no difference between protein or mRNA expression of ATGL, G0S2, and CGI-58. CONCLUSION: LPS stimulated lipolysis in adipose tissue and is associated with increased pHSL and signs of increased PLIN1 phosphorylation combined with a trend toward decreased insulin signaling. The combination of these mechanisms appear to be the driving forces behind the increased lipolysis observed in the early stages of acute inflammation and sepsis. TRIAL REGISTRATION: ClinicalTrials.gov NCT01705782